2020
DOI: 10.3390/w12102787
|View full text |Cite
|
Sign up to set email alerts
|

Water and Land as Shared Resources for Agriculture and Aquaculture: Insights from Asia

Abstract: Although agriculture and aquaculture depend on access to increasingly scarce, shared water resources to produce food for human consumption, they are most often considered in isolation. We argue that they should be treated as integrated components of a single complex system that is prone to direct or indirect tradeoffs that should be avoided while also being amenable to synergies that should be sought. Direct tradeoffs such as competition for space or the pollution of shared water resources usually occur when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 210 publications
(297 reference statements)
1
10
0
1
Order By: Relevance
“…Similar to several earlier studies, this study shows that the reuse and recycling of nutrients in integrated aquaculture and agricultural systems help to improve the efficiency of food production and help to reduce pollution by excessive nutrients, thereby contributing to improved living conditions for farmers through increased income and environmental health (Berg, 2002;Drózdz et al, 2020;Pueppke et al, 2020;Ahmed and Turchini, 2021;Farrant et al, 2021). We found that chemical fertilizer supplemented with 25 and 50% of organic fertilizers applied to the soil had a significant positive impact on the growth performance indices of Malabar spinach and Amaranthus cruentus and resulted in the highest final yield of these vegetables.…”
Section: Benefits Of Organic Fertilizers For Vegetables and Soil Qualitysupporting
confidence: 84%
“…Similar to several earlier studies, this study shows that the reuse and recycling of nutrients in integrated aquaculture and agricultural systems help to improve the efficiency of food production and help to reduce pollution by excessive nutrients, thereby contributing to improved living conditions for farmers through increased income and environmental health (Berg, 2002;Drózdz et al, 2020;Pueppke et al, 2020;Ahmed and Turchini, 2021;Farrant et al, 2021). We found that chemical fertilizer supplemented with 25 and 50% of organic fertilizers applied to the soil had a significant positive impact on the growth performance indices of Malabar spinach and Amaranthus cruentus and resulted in the highest final yield of these vegetables.…”
Section: Benefits Of Organic Fertilizers For Vegetables and Soil Qualitysupporting
confidence: 84%
“…Most of the previous studies consider the ecosystem of a region as a whole and study the ecosystem of different land use types as an integral part but neglect differences among different land use types in the ecosystem. Some studies found that cultivated lands would be occupied for the expansion of aquaculture ponds [ 59 ], but few studies estimated the ESV change. In consideration of the urgency of the phenomenon, the study selects cultivated lands and aquaculture ponds to independently analyze their ESV changes, which will improve research in the field.…”
Section: Discussionmentioning
confidence: 99%
“…With a look at the scarce water resources and the increasing food demand and energy sources, it is essential to look at both synergies and trade-offs. It can be dealt with holistically through the lens of the water-food-energy nexus rather than dealing with them in silos and looking at short-term economic incentives [ 56 ].…”
Section: Discussionmentioning
confidence: 99%